Structure of Nonionic Surfactant Diglycerol Monomyristate Micelles in Cyclohexane: a SAXS Study - Shrestha, Lok Kumar (Journal of Nepal Chemical Society, 2009)
Structure of nonionic surfactant diglycerol monomyristate (C14G2) micelles in cyclohexane has been investigated by small-angle X-ray scattering (SAXS) technique. Structural modulation of reverse micelle (RM) has been systematically studied by changing composition, temperature change and added-water. The SAXS data were evaluated by the generalized indirect Fourier transformation (GIFT) method, which gives pair-distance distribution function (PDDF). Unlike conventional poly(oxyethylene) type nonionic surfactants, C14G2 forms RM in cyclohexane without water addition at normal room temperature. A clear indication of one dimensional (1-D) micellar growth was found with increasing C14G2 concentrations. On the other hand, temperature induced cylinder-to-sphere type transition in the RM structure. The maximum dimension and the cross-sectional diameter of the RM increased upon addition of trace water indicating the formation of water pool in the reverse micellar core.Keywords: Diglycerol monomyristate, small-angle X-ray scattering, reverse micelles.DOI: 10.3126/jncs.v23i0.2099J. Nepal Chem. Soc., Vol. 23, 2008/2009Page: 74-81